Recent advances in understanding prodrug transport through the SLC15 family of proton-coupled transporters. (27th March 2020) - Minhas, Gurdeep S.; Newstead, Simon
Abstract : Solute carrier (SLC) transporters play important roles in regulating the movement of small molecules and ions across cellular membranes. In mammals, they play an important role in regulating the uptake of nutrients and vitamins from the diet, and in controlling the distribution of their metabolic intermediates within the cell. Several SLC families also play an important role in drug transport and strategies are being developed to hijack SLC transporters to control and regulate drug transport within the body. Through the addition of amino acid and peptide moieties several novel antiviral and anticancer agents have been developed that hijack the proton-coupled oligopeptide transporters, PepT1 (SCL15A1) and PepT2 (SLC15A2), for improved intestinal absorption and renal retention in the body. A major goal is to understand the rationale behind these successes and expand the library of prodrug molecules that utilise SLC transporters. Recent co-crystal structures of prokaryotic homologues of the human PepT1 and PepT2 transporters have shed important new insights into the mechanism of prodrug recognition. Here, I will review recent developments in our understanding of ligand recognition and binding promiscuity within the SLC15 family, and discuss current models for prodrug recognition.